SURVEY 1-HOUR BUNDLE COMPLIANCE IN CARE OF SEPSIS AND SEPTIC SHOCK PATIENTS AT THONG NHAT HOSPITAL - Công Thuyên, Lê; Tấn Đạt, Nguyễn; Đức Tới, Nguyễn (Journal of Health and Aging, 2025)
Survey compliance with the 1-hour sepsis bundle in patients with sepsis and septic shock at Thong Nhat hospital and analyze the relation between compliance with the 1-hour bundle and patient’s outcomes. A retrospective study was conducted on 55 patients admitted to the Emergency Department of Thong Nhat Hospital from January 2024 to July 2024. Patients were selected based on the diagnostic criteria for sepsis in Sepsis-3 definition with no prior treatment. Compliance with the 1-hour sepsis bundle was assessed, including blood culture collection, initiation of antibiotics, fluid resuscitation, lactate measurement, and vasopressor administration when needed. In 55 patients included in the study, male accounted for 50.1%; proportion of female was 49.1% with mean age was 79 ± 18.35. According ro the diagnosis of emergency doctors, there were 43/55 (78.2%) cases of sepsis and 12/55 (21.8%) cases of septic shock. The history of hypertension was the majority (65.5%) with the most common focus of infection being the respiratory tract (54.5%), urinary tract (30.9%), of which 14 cases had 2 or more foci of infection. Regarding compliance with the one-hour bundle in the care of patients with sepsis and septic shock, 35/55 (63.6%) completed the one-hour package and 25.4% did not complete it. Adherence to the one-hour bundle in primary analyses showed improved mortality in patients with sepsis and septic shock with OR = 5.07 (p < 0.05). Our study showed that proportion of one-hour bundle compliance had improved over time, with increasing clinical application. It also demonstrated the effectiveness and importance of adherence to the one-hour bundle in improving sepsis and septic shock patient survival.
Keywords: 1-hour bundle; Sepsis; Septic shock